Australian diver. (Brisbane : Penrod Publishers Pty, Ltd., 1969)
The monthly magazine published in the interests of Skin and Scuba Diving throughout Australia.
Title from cover.
Description based on: Vol. 1, no. 3 (December 1969)
Keywords: Scuba diving -- Australia -- Periodicals; Deep diving -- Australia -- Periodicals; Scuba divers -- Australia -- Periodicals; Australian